2021
DOI: 10.1080/10826084.2020.1869264
|View full text |Cite
|
Sign up to set email alerts
|

Pulling Your Mask down to Smoke: Qualitative Themes from Young Adults on Nicotine Use during a Pandemic

Abstract: Introduction:The COVID-19 pandemic may have resulted in a change in life routines for tobacco users, but little is known about the rationale underlying these changes. Methods: A convenience sample of young adults ages 21-28 (n ¼ 29) were recruited online May-July 2020 to participate in semi-structured interviews about nicotine use behaviors specific to cigarillos and e-cigarettes. Audio-recorded interviews were 60-90 min long and were conducted remotely. Participants were asked opinions and behavioral effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…Prior research has also documented both increased and decreased smoking during the pandemic [9,10,12], with people reporting a variety of reasons for changes in their smoking, such as disrupted schedules and social situations [12,[14][15][16], financial and logistical constraints [12,15,16], and stress [12,[14][15][16]. While health concerns of smoking and COVID-19 contributed to decreased smoking [12,[14][15][16], other factors were also influential. Other studies using the HBM to predict behavior and behavioral intentions during the pandemic [21][22][23][24][25][26][27][28][29][30] have also produced mixed results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research has also documented both increased and decreased smoking during the pandemic [9,10,12], with people reporting a variety of reasons for changes in their smoking, such as disrupted schedules and social situations [12,[14][15][16], financial and logistical constraints [12,15,16], and stress [12,[14][15][16]. While health concerns of smoking and COVID-19 contributed to decreased smoking [12,[14][15][16], other factors were also influential. Other studies using the HBM to predict behavior and behavioral intentions during the pandemic [21][22][23][24][25][26][27][28][29][30] have also produced mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived stress from the pandemic was significantly associated with both increased smoking and decreased smoking. Prior research has also documented both increased and decreased smoking during the pandemic [ 9 , 10 , 12 ], with people reporting a variety of reasons for changes in their smoking, such as disrupted schedules and social situations [ 12 , 14 , 15 , 16 ], financial and logistical constraints [ 12 , 15 , 16 ], and stress [ 12 , 14 , 15 , 16 ]. While health concerns of smoking and COVID-19 contributed to decreased smoking [ 12 , 14 , 15 , 16 ], other factors were also influential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a growing body of literature has qualitatively explored the psychological and societal impact of the COVID-19 outbreak, age-specific data, particularly regarding older age, is still lacking [15]. Most studies have addressed the impact of COVID-19 on health-care providers, patients, caregivers and children [20][21][22][23][24][25]. However, most studies were conducted in China with very small samples.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported increases in cessation and quit attempts [ 9 ], and increased motivation to quit for some study participants [ 10 ], potentially reflecting concerns about contracting Covid-19 and becoming severely ill as a result [ 7 , 8 ]. A few studies have reported changes in tobacco purchasing patterns, with some cigarette smokers having large stocks of cigarettes at home to avoid leaving the house every day to purchase more [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%